Analisis Yuridis Kedudukan Instruksi Presiden dalam Sistem Hukum Nasional - Mayolla Octavia; Laila Mauluda Tunnisa (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
Presidential Instructions (Inpres) are not regulated within the hierarchy of national laws and regulations, but are still widely used as an administrative instrument in government practice. This raises legal problems related to the status and binding force of Inpres within the Indonesian legal system. To address this issue, this research employs a normative legal approach with a descriptive-analytical method through literature studies on regulations and legal doctrines. The research findings indicate that Inpres has an internal administrative nature and is only binding on officials within the executive structure, but it can affect society if used as a basis for issuing administrative actions. It is concluded that although not a piece of legislation, Inpres still has limited legal consequences and must adhere to the principle of legality and the principles of good governance.